1992
DOI: 10.1007/bf00043472
|View full text |Cite
|
Sign up to set email alerts
|

The effect of asparagus virus infection on asparagus tissue culture

Abstract: The impact of asparagus virus I (AV-I), a potyvirus, and asparagus virus II (AV-II), an ilarvirus, on micropropagation of field-grown asparagus was studied. Apical shoot tips excised from singly or doubly-infected plants were slow to develop roots and had a 15 to 75% reduction in survival in culture, respectively, compared to those excised from virus-free plants. The four virus infection groups were ranked: virus-free > AV-II > AV-I >AV-I & II for capacity of explants to both root and survive in vitro.Micropro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…(, ) also found GRLaV‐3 reduced root formation in the virus‐infected in vitro shoots. A number of examples of reduced vegetative growth and rooting can be found in other virus–host combinations such as Asparagus officinalis infected by Asparagus virus I (AV‐I, De Vries‐Paterson et al ., ), Rubus idaeus infected by tobacco streak virus (TSV) or raspberry bushy dwarf virus (RBDV) or tomato ringspot virus (TomRSV) (Tsao et al ., ), Citrus infected by Citrus tristeza virus (CTV) (Wang et al ., ), Musa infected by banana bunchy top virus (BBTV, Haq et al ., ) and potato leafroll virus or potato virus Y (Li et al ., ). All of these studies support ours.…”
Section: Discussionmentioning
confidence: 99%
“…(, ) also found GRLaV‐3 reduced root formation in the virus‐infected in vitro shoots. A number of examples of reduced vegetative growth and rooting can be found in other virus–host combinations such as Asparagus officinalis infected by Asparagus virus I (AV‐I, De Vries‐Paterson et al ., ), Rubus idaeus infected by tobacco streak virus (TSV) or raspberry bushy dwarf virus (RBDV) or tomato ringspot virus (TomRSV) (Tsao et al ., ), Citrus infected by Citrus tristeza virus (CTV) (Wang et al ., ), Musa infected by banana bunchy top virus (BBTV, Haq et al ., ) and potato leafroll virus or potato virus Y (Li et al ., ). All of these studies support ours.…”
Section: Discussionmentioning
confidence: 99%
“…Igor infected with potato virus Y NTN accumulates jasmonic acid in the roots, and roots are significantly shorter, but there are no significant differences in the average length of infected and healthy potato plantlets (Petrovic et al, 1997). Fresh and dry weights of infected potato shoots and roots are reduced but no in vitro shoot symptoms appear, such as the stunting, necrosis, and mosaic patterns normally observed on field plants (De Vries-Paterson et al, 1992;Petrovic et al, 1997). The only case of virus and virus-like agents affecting both the number and size of shoots produced is in nodal citrus-stem segments (Greno et al, 1988).…”
Section: Resultsmentioning
confidence: 95%
“…It is known that virus-infected tissue can have reduced in vitro growth compared to non-infected tissue. De Vries-Paterson et al (1992) first reported the effects of single and two-virus infections in reducing asparagus in vitro root development, survival in culture, and the fresh and dry weights of micropropagated plants. In vitro shoot-tip culture alone, without other virus-elimination treatments, resulted in only 8.6% virus-free asparagus clones.…”
Section: Introductionmentioning
confidence: 98%
“…Apparently TropMV is an easy virus to eliminate from mashua compared to other plant-virus combinations (De Vries-Paterson et al ., 1992; Zapata et al ., 1995) as 83% of the apical dome-derived plants tested free of TropMV. This may have been due to characteristics of TropMV and/or size of apical dome.…”
Section: Discussionmentioning
confidence: 99%
“…Apical dome culture is one technique that has been used to produce virus-tested germplasm in a number of crops (De Vries-Paterson et al ., 1992; Zapata et al ., 1995). Protocols for initiating and maintaining mashua in vitro have been developed (Estrada et al ., 1986; Perea-Dallos et al ., 1986).…”
Section: Introductionmentioning
confidence: 99%